PENGARUH SENAM LANSIA TERHADAP TINGKAT NYERI LUTUT PADA LANSIA DI RW 02 DESA KAYU BONGKOK KEC. SEPATAN KAB. TANGERANG - Fuji Lestari (Nusantara Hasana Journal, 2022)
The elderly are susceptible to changes in physical conditions such as decreased ability of the musculoskeletal system. This decrease is indicated by the presence of pain in the joint area. Knee pain is a regenerative disease problem that often occurs in the elderly, measures to reduce knee pain in the elderly can be in the form of non-pharmacological therapy such as elderly exercise. Research objectives to determine the effect of elderly exercise on knee pain levels in the elderly in RW 02 Kayu Bongkok Village, Kec. Kab. Tangerang. This type of research is quantitative, the design of this study uses the Pre-Experimental method with the One Group Pre-Test Post-Test Design. The number of samples in the study were 30 elderly people with purposive sampling technique. The instruments used are Numerical Rating Scale pain scale and exercise observation sheet. The statistical tests used in this study were the Wilcoxon signed ranks test and the paired t-test. Based on the results of statistical tests using the Wilcoxon signed ranks test, it is known that the Z value in the Pre-Post variable knee pain level is -4.774 with a p value of Asymp. Sig. (2-tailed) of .000 < 0.05, it can be concluded that "Ha/H1 is accepted" meaning that there is a difference between the results of knee pain levels before and after elderly exercise. The results of the paired t-test have p value or sig 0.000, which means (p<α = 0.05). it is stated that H0 is rejected and Ha/H1 is accepted or 'Hypothesis is accepted', meaning that it can be concluded that the influence of knee pain levels before and after elderly exercise is carried out in RW 02 Kayu Bongkok Village, Kec. Sepat Kab. Tangerang. There is an effect of elderly exercise on knee pain levels in the elderly in RW 02 Kayu Bongkok Village, Kec. Kab. Tangerang.